Investigating the effects of partitioning temperature fluctuations on the mechanical properties of ASTM A36 carbon steel using Q-P-T heat treatment: an experimental study - Alief Muhammad; Mochamad Fani Nur Umri; Muhammad Fathuddin Noor; Dani Hari Tunggal Prasetyo; Indah Noor Dwi Kusuma Dewi; Angga Prasmana; Mas Ahmad Baihaqi; Hartawan Abdillah (Jurnal Polimesin, 2024)
In the continuum of time and technological advancement, the use of metals, specifically carbon steel, has significantly increased as primary materials in various operational and industrial domains, including tool fabrication and automotive components. To meet the evolving demands of industries, precise heat treatment processes have been developed to enhance the metallic properties. This study specifically focused on the application of the Quenching-Partitioning-Tempering (Q-P-T) method to ASTM A36 steel. The study investigated different partitioning temperatures, namely 300℃, 350℃, and 400℃, with 15-minute intervals. A comprehensive set of mechanical tests, including hardness, tensile, and microstructural analyses, were conducted to assess the response of the material to the treatment. The results reveal significant findings: a partitioning temperature of 300℃ yields the highest hardness value of 164 Vickers Hardness Number (VHN). Furthermore, the tensile tests demonstrate that a partitioning temperature of 300℃ is optimal, achieving a maximum stress value of 515.73 MPa. Conversely, a partitioning temperature of 400℃ exhibits the highest strain value at 21.08% and the highest elastic modulus value at 11.47 GPa. Microstructural evaluations highlighted the presence of pearlite and ferrite phases, with the partitioning temperature of 300°C displaying the highest proportion of pearlite phase at 38.5%. This meticulous investigation expands our understanding of metallurgy and underscores the intricate relationship between partitioning temperatures and the mechanical properties of ASTM A36 steel. It provides valuable insights for material design and application methodologies and facilitates advancements in industrial practices